Measuring Globalization : Better Trade Statistics for Better Policy - Mandel, Michael J.; Houseman, Susan N., 1956-; Project Muse. (Kalamazoo, Michigan : W.E. Upjohn Institute for Employment Research, 2015)
Understanding the impacts of globalization requires good data, and national statistical systems were not designed to measure many of the transactions occurring in today$1 (Bs global economy. The chapters in this two-volume set identify biases and gaps in national statistics, examine the magnitude of the problems they pose, and propose solutions to address significant biases and fill key data gaps.s
Volume 1. Biases to price, output, and productivity statistics from trade -- Volume 2. Factoryless manufacturing, global supply chains, and trade in intangibles and data.
Description based on print version record.
Keywords: Commercial statistics; BUSINESS & ECONOMICS -- Structural Adjustment; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs; BUSINESS & ECONOMICS -- International -- Marketing; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- Exports & Imports; Commercial statistics; Electronic books